DOKTRIN ALLAH/PROPER - Yugi Stepanus; Kana, Lukas Thelios Ranogin, Sarmauli (ADISAM PUBLISHER, 2024)
This paper discusses the doctrine of God within the context of Christian theology, exploring important aspects such as definitions, the names of God in the Old and New Testaments, and denials of His existence. The research aims to provide a deeper understanding of the nature and role of God in human life. Additionally, the paper explores secular theories that attempt to explain God's existence, as well as biblical evidence supporting the belief in His existence. Through a theological approach and critical analysis, this paper is expected to serve as a reference for students, academics, and practitioners in understanding effective conflict management in a religious context. By gaining a better understanding of the doctrine of God, it is hoped that readers can apply these values in their daily lives to create harmony and peace in social interactions